IMPLEMENTASI PROGRAM JEMPOL DALAM MENINGKATKAN KUALITAS PELAYANAN KTP-EL BAGI PENYANDANG DISABILITAS DI KABUPATEN DARI PROVINSI SUMUT - Hotlina Sihombing; Muhammad Faisal (Jurnal Pallangga Praja (JPP), 2022)
Dairi Regency is a district in North Sumatra Province. In Law Number 19 of 2011 concerning the Ratificationof the Rights of Persons with disabilities. with problems related to administrative services, the dairiRegency government has made improvements to population administration services in order to improve thebad image that exists in the community. The innovation implemented by the disdukcapiI of dairi Regency isthe Population administration Jemput Bola Program (JeMPoL). The Jemput Bola program for people withdisabilities began to be implemented in dairi Regency in 2019. The type of research used in this researchis a descriptive type of research with a qualitative approach. The results of this study indicate that theimplementation of the Jemput Bola program in improving e-KTP services for persons with disabilities hasbeen carried out well, but not optimally.